Rapid Detection and Antimicrobial Susceptibility Testing of Pathogens Using AgNPs-Invertase Complexes and the Personal Glucose Meter - Zheng, Laibao; Shen, Yunqiu; Dong, Wenjia; Zheng, Chaochuan; Zhou, Ruolan; Lou, Yong-Liang (Frontiers in Bioengineering and Biotechnology, 2022)
Rapid detection of pathogens and assessment of antimicrobial susceptibility is of great importance for public health, especially in resource-limiting regions. Herein, we developed a rapid, portable, and universal detection method for bacteria using AgNPs-invertase complexes and the personal glucose meter (PGM). In the presence of bacteria, the invertase could be released from AgNPs-invertase complexes where its enzyme activity of invertase was inhibited. Then, the enzyme activity of invertase was restored and could convert sucrose into glucose measured by a commercially PGM. There was a good linear relationship between PGM signal and concentration of E. coli or S. aureus as the bacteria model with high sensitivity. And our proposed biosensor was proved to be a rapid and reliable method for antimicrobial susceptibility testing within 4 h with consistent results of Minimum Inhibitory Concentrations (MICs) testing, providing a portable and convenient method to treat infected patients with correct antibiotics and reduce the production of antibiotic-resistant bacteria, especially for resource-limiting settings.